K-wire osteosynthesis for arthrodesis of the paediatric foot is a good and valid procedure - Kreher, Jannes; Putz, Cornelia; Fackler, Susanne; Müller, Sebastian; Horsch, Axel; Geisbüsch, Andreas (Journal of Clinical Medicine, 2023)
Background: Foot deformities in children are common, and the majority can be treated conservatively. Nevertheless, there are deformities that require surgical treatment. These include rigid clubfeet, severe forms of pes planovalgus, pes cavus and several more. We retrospectively analysed the pseudarthrosis rate of surgical treatment of foot deformities with transcutaneous K-wire osteosynthesis in neurologically healthy children and adolescents. The aim of the study was to show that the results with K-wires are comparable to those with other osteosynthesis methods in the literature. Methods: A total of 46 paediatric patients aged 6 to 17 years treated between January 2010 and December 2015 met the inclusion criteria. Depending on the diagnosis, different surgical interventions were necessary. In clubfoot and pes planovalgus, representing n = 81, 70% of the whole collective triple arthrodesis with fusion of the talonavicular, calcaneocuboid and subtalar joints or Evans osteotomy was usually performed. Radiographs were taken at least 6 months post-surgery, and bony consolidation of the subtalar, talonavicular (TN), and calcaneocuboidal (CC) joints and the metatarsal I (MT I) osteotomy were assessed. If there was no evidence of fusion at this time, it was considered non-union. Results: In total, 117 arthrodesis procedures with K-wires were performed. Overall, 110 of the arthrodesis (94%) healed, and only 7 joints (6%) showed non-union (subtalar 0%, TN 7.7%, CC 6.5% and MT I 6.7%). All non-unions occurred in subjects with clubfoot deformities. No significant risk factors were observed. Conclusion: This study replicated the good consolidation rates reported in the literature with screws, plates, intramedullary nails or staples in arthrodesis of the adolescent foot in neurologically healthy subjects and confirmed the efficacy of K-wires. The main advantages of transcutaneous K-wire treatment are easy metal removal, lower osteosynthesis material costs and less concomitant damage. Further studies, especially randomised controlled trials, are needed to further investigate this topic.
Gesehen am 19.01.2024